Initial evaluation of a public transportation training program for individuals with intellectual and developmental disabilities: Short report. (March 2020) - Pfeiffer, Beth; Sell, Annalisa; Bevans, Katherine B.
Abstract: Introduction: People with intellectual and developmental disabilities (IDD) including Autism Spectrum Disorders (ASD) often face serious transportation challenges that impede healthcare access, community participation, and employment opportunities. Travel training, which makes use of one-on-one instruction, may help people with IDD overcome transportation barriers. The purpose of this study was to examine the impact of a comprehensive travel training program on the travel skills of individuals with IDD. Methods: Participants were a convenience sample of all individuals with IDD (n = 87) who received travel training from the Kennedy Center in 2016 and 2017. Pre- and post-test scores on the Progressive Evaluation of Travel Skills, as well as primary mode(s) of public transportation used, purpose of use, and number of training sessions were recorded in a secure database. Data was de-identified which involved a process of removing any personally identifiable information. A secondary analysis was completed to test the effect of travel training on transportation skill acquisition by using multilevel analyses. Specifically, the effects of condition (Intellectual Disability (ID) without ASD, ID and ASD, ASD without ID), time (pre-training, post-training), and condition x time interactions on transportation skill T-scores were analyzed. Results: Participants were 69 men and 18 women with IDD and/or ASD (mean age = 23.6). Trainees made statistically significant gains on the competencies needed for independent travel. A significant condition x time (training) interaction was observed. Prior to training, people with ID (with and without ASD) had less developed travel skills than those with ASD (and no ID). Upon completion of the training, those with ID made larger gains in travel skills than those with ASD/no ID in which both groups had comparable skill levels. Conclusions: The results of this study provide preliminary support for the use of a structured and comprehensive travel training program to improve overall travel skills needed for public transportation. Highlights: Individuals with IDD obtained skills needed to use public transportation after a structured travel training program. People with ID made larger gains than those with ASD and no ID resulting in comparable travel skills at the end of the study. Results provide support for a comprehensive travel training program to improve skills needed for public transportation.